Sexual Harassment Through Language Strategies of Power in Higher Education Based on the Trichotomy of Relationships Approach - Liza Agnesta Krisna; Rocky Marbun (Jurnal Dinamika Hukum, 2024)
Women are considered vulnerable under the UN Charter of Human Rights due to many factors, two of which are historical and systemic marginalization. Women, as a vulnerable group, increase their chances of becoming victims of sexual harassment, both physical and verbal abuse. This practice occurs across various settings, including Higher Education environments where such behaviors against students are prevalent. Legal science is no longer superior in reaching holistically when there is an inability to track language strategies based on the unconscious marginalization of binary opposition. This article aims to shed light on the ideological interests concealed behind a semantic model and the spread of semiotic symbols with sexual connotations. Using the legal research method with a Trichotomy of Relations approach, it uncovers the glorification of social status - as a lecturer, as capital in creating instrumental communication with sexual connotations. Regulations are needed to combat the misuse of communication for power and remove barriers hindering meaningful discourse. This policy should also enforce the use of clear and formal language to minimize interpretational ambiguities within the institution.Keywords: Criminal Law; Sexual Harassment; Trichotomy of Relation.